An appellate body for international investment disputes: How appealing is it? - Joachim Karl (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
One suggestion in the ISDS reform debate relates to the establishment of an appellate body. This Perspective considers that an ad-hoc appellate body agreed upon in new investment treaties would be the most promising alternative. However, only a permanent appellate body could ensure coherence and predictability in global arbitration practice.
Keywords: 330